Eu sou MC: participação coletiva e plural de mulheres em cenas musicais RAP - Mazer, Dulce (2018)
The text approaches the dynamics of young women acting on rap scenes in the capital of Rio Grande do Sul (Brazil) in order to reflect on the communicational aspects of their different roles and functions through the mediatization of their performances. Thus, the article is based on an ethnography of rap scenes from the Metropolitan Region of Porto Alegre (RMPA) - RS, Brazil, conducted between 2014 and 2017. Our empirical research, which guides the discussions presented, resulted in a deepening of the practices of expanded musical consumption among young people participating in (sub) hip-hop culture, which involves the production and consumption of rap. As general results of what weve proposed, we analyzed the main practices of girls or groups of women who compose and perform rap music in order to understand how they have been reconfiguring gender relations in hip-hop (sub)culture